PROGRAM PLAN FOR IMPROVING INTERPERSONAL RELATIONS IN THE TEAM - Самойленко, Олена; Корнєєва, Олена; Шундель, Тетяна (SWorldJournal, 2023)
The article presents a thematic plan of a program for improving interpersonal relationships in a team or groups, which can be used for trainings with teenagers and adults over 13 years old.In the program, which is designed for 30 hours, the tasks reframi